Microsurgical technique for end to end anastomosis in vessels with large díameter disproportion - Fossati, Enrique; Asurey, Néstor; Irigaray, Alberto (Cirugía del Uruguay, 1988)
A microsurgical technique to perform end to end anastomosis between vessels with very importan! diameter dillerences is presented. Clinical and experimental results are commented. Advantages of the procedure are pointed out.